Methanogenesis Inhibition in Anaerobic Granular Sludge for the Generation of Volatile Fatty Acids from CO2 and Zero Valent Iron - Samanides, Charis G.; Koutsokeras, Loukas; Constantinides, Georgios; Vyrides, Ioannis (Frontiers in Energy Research, 2020)
A new approach for CO2 utilization (as a sole carbon source) to acetic acid and other VFAs under ambient conditions using zero valent iron and anaerobic granular sludge was examined by methanogens inhibition. Zero Valent Iron when is anaerobically oxidized generates H2 that can be utilized along with CO2 by homoacetogens in the anaerobic granular sludge for the production of acetic acid or other VFAs. However, methanogens in anaerobic sludge act antagonistically with homoacetogens and therefore the main goal of this study is to examine strategies to inhibit methanogenesis and to enrich homoacetogens. Based on this, several strategies were investigated such as the exposure of (a) anaerobic granular sludge to low pH, (b) the short exposure of anaerobic granular sludge to heat, (c) addition of bromoethanesulfonate under various concentrations and (d) exposure of anaerobic granular sludge to salinity 30–90 g NaCl/L. The highest performance (2,020 mg/L of acetic acid) was found when anaerobic granular sludge was exposed to 50 mM of bromoethanesulfonate at 100 g/L (ZVI), pH 6–6.5, after 12 days whereas, the short exposure of anaerobic granular sludge to heat at 100 g/L ZVI at pH 6–6.5 resulted in 1,290 mg/L of acetic acid. The operation of this system in pH 5–6 generated less VFAs compared to operation at pH 6–6–5. The daily regulation of pH to 3 was not practical as the pH was increased to 6.5 due to abiotic anaerobic oxidation of ZVI and this resulted in CH4 production and propionic acid generation. The exposure of anaerobic granular sludge to ZVI and 30 g NaCl/L as well as to seawater resulted in production of CH4 (around 28% of the headspace) and mainly production of acetic acid (550–850 mg/L). The increased in salinity to 60 and 90 g NaCl/L resulted in reduction of CH4 and VFAs however, a more diverse range of VFAs was produced. Exposure of anaerobic granular sludge to heat and then to CO2 and ZVI resulted in an increase of Clostridium sensu stricto to 65.9% and the same genus was increased when anaerobic sludge was exposed to bromoethanesulfonate and ZVI.